Future Perspective for ALK-Positive Anaplastic Large Cell Lymphoma with Initial Central Nervous System (CNS) Involvement: Could Next-Generation ALK Inhibitors Replace Brain Radiotherapy for the Prevention of Further CNS Relapse? - Makito Tanaka; Hiroki Miura; Soichiro Ishimaru; Gen Furukawa; Yoshiki Kawamura; Kei Kozawa; Seiji Yamada; Fumitaka Ito; Kazuko Kudo; Tetsushi Yoshikawa (MDPI AG, 2023)
Central nervous system (CNS) involvement in anaplastic large cell lymphoma (ALCL) at diagnosis is rare and leads to poor prognosis with the use of the standard ALCL99 protocol alone. CNS-directed intensive chemotherapy, such as an increased dose of intravenous MTX, increased dose of dexamethasone, intensified intrathecal therapy, and high-dose cytarabine, followed by cranial irradiation, has been shown to improve survival in this population. In this paper, the authors describe a 14-year-old male with an intracranial ALCL mass at onset who received CNS-directed chemotherapy followed by 23.4 Gy of whole-brain irradiation. After the first systemic relapse, the CNS-penetrating ALK inhibitor, alectinib, was applied; it has successfully maintained remission for 18 months without any adverse events. CNS-penetrating ALK inhibitor therapy might prevent CNS relapse in pediatric ALK-positive ALCL. Next-generation ALK inhibitors could be introduced as a promising treatment option, even for primary ALCL with CNS involvement, which could lead to the omission of cranial irradiation and avoid radiation-induced sequalae. Further evidence of CNS-penetrating ALK inhibitor combined therapy for primary ALK-positive ALCL is warranted to reduce radiation-induced sequalae in future treatments.